2010
DOI: 10.1186/1471-2458-10-11
|View full text |Cite
|
Sign up to set email alerts
|

Computer-associated health complaints and sources of ergonomic instructions in computer-related issues among Finnish adolescents: A cross-sectional study

Abstract: BackgroundThe use of computers has increased among adolescents, as have musculoskeletal symptoms. There is evidence that these symptoms can be reduced through an ergonomics approach and through education. The purpose of this study was to examine where adolescents had received ergonomic instructions related to computer use, and whether receiving these instructions was associated with a reduced prevalence of computer-associated health complaints.MethodsMailed survey with nationally representative sample of 12 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 15 publications
4
23
0
1
Order By: Relevance
“…Results of researchers revealed further that uses of computer precipitates hurt and discomfort on cervico-pectoral region, along the spine, fingers, eyes and head (33,34,36,37). Our finding also supported the report of these studies.…”
Section: Discussionsupporting
confidence: 88%
“…Results of researchers revealed further that uses of computer precipitates hurt and discomfort on cervico-pectoral region, along the spine, fingers, eyes and head (33,34,36,37). Our finding also supported the report of these studies.…”
Section: Discussionsupporting
confidence: 88%
“…Advancing age was another associated risk for PAD in this study, which was also reported as a risk in previous studies [ 11 , 17 , 36 ]. Association of PAD with advancing age may be explained by the fact that the incidence of other risk factors associated with atherosclerosis, such as diabetes and hypertension, also increases with age [ 12 , 37 ].…”
Section: Discussionsupporting
confidence: 88%
“…Todd et al [38] stated that long-term sitting and long-term static posture may increase upper and lower back pain risk, while Myrtveit et al [25] stated that excessive time spent on screen-based activities can increase the risk of neck and shoulder pain. Since the musculoskeletal complaints are acute, chronic and repetitive, it is considered as a public health problem [11,12]. The purpose of this study was to examine the smartphone using university students' 1) musculoskeletal system pain complaints, 2) duration of smartphone and computer usage, 3) participation in moderate-vigorous physical activities (MVPA), and 4) prolonged sitting time.…”
Section: Introductionmentioning
confidence: 99%